2005
DOI: 10.1111/j.1601-0825.2004.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Tongue disease in advanced AIDS

Abstract: These findings indicate that the tongue is a favorite site to occurrence of reactive, infectious and concurrent lesions in the end-stage of AIDS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
3
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
2
15
3
4
Order By: Relevance
“…This rate is lower than other studies 5,13 , in which mouth was much more commonly affected. This difference is probably due to methodology used, because, instead of the cited work 5 , we did not do a global study of oral cavity, but only of tongue.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…This rate is lower than other studies 5,13 , in which mouth was much more commonly affected. This difference is probably due to methodology used, because, instead of the cited work 5 , we did not do a global study of oral cavity, but only of tongue.…”
Section: Discussioncontrasting
confidence: 48%
“…This difference is probably due to methodology used, because, instead of the cited work 5 , we did not do a global study of oral cavity, but only of tongue. In our study we found 8% of cases of oral hairy leukoplakia, while other works found this lesion as the most frequent, present in 35.5% of 45 autopsies and in 45.6% of 92 autopsies, respectively 5,13 . It is possible that some of this difference is related to sampling for microscopy.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…2,3 An important line of investigation by our group refers to the study of the oral alterations found during autopsy in patients who had died due to complications of human immunodeficiency virus infection. 4,5 Although not a common field of study by oral pathologists, autopsybased investigations represent an unmeasured source of data for better understanding the oral manifestations of systemic diseases, especially in developing countries, where infections still represent major causes of death. The microscopic analysis of autopsies can also provide a better comprehension of normal structures not commonly evaluated in regular oral biopsies, such as the posterior area or the base of the tongue.…”
Section: To the Editormentioning
confidence: 99%
“…Many of these HIV-positive patients present manifestations involving the maxillofacial region in all stages of the disease, and, in some cases, the oral lesions are the first signs of infection. [910] With disease progression, the deleterious effect of HIV on the immune system results in an escalating incidence of widely recognized and extensively described OIs and diseases, among which are the oral manifestations of HIV and, since the onset of the HIV pandemic, oral lesions have been well documented as early markers of HIV infection and as predictors of HIV disease progression. [1112] Oral manifestations can suggest decreased cluster-differentiated 4 (CD4+) T cell count and increased viral load, which might also aid in the diagnosis, progression, and prognosis of the disease.…”
Section: Introductionmentioning
confidence: 99%